(3GdJMdjd GdEbJUGOj Gdcdj hGdLRFjs - (3GSeGYjd(B, (3YHO GdQMefs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2004)
(3eaGgje CSGSjI aj Yde GdEbJUGO(B- (3MSGHGJ GdONd Gdbhej(B- (3fXQjI GdESJgdGc(B- (3JNWjW GdESJKeGQ(B- (3fXQjI GdEONGQ(B- (3GdHWGdI(B- (3GdJVNe(B- (3GdSjGSI GdeGdjI(B- (3GdfbhO hGdeUGQa(B- (3GdJLGQI GdNGQLjI(B- (3GdJfejI GdEbJUGOjI hGdfeh GdEbJUGOj(B- (3GdJNWjW GdEbJUGOj(B- (3fXQjGJ GdbjeI(B- (3fXQjGJ GdWdH(B- (3fXQjI GdYQV(B- (3JhGRf GdWdH hGdYQV(B- (3fXQjI Sdhc GdeSJgdc(B- (3fXQjI GdEfJGL(B- (3fXQjI JcGdja GdEfJGL(B- (3fXQjI GdJhRjY(B- (3fXQjI GdGShGb(B- (3JhGRf GdefJL aj MGdGJ GdGShGb GdeNJdaI(B.s
Keywords: (3GdEbJUGO GdLRFjs; (3GdEbJUGO Gdcdjs; (3GdfXe GbJUGOjIs